Peran Masyarakat dalam Mempertahankan Budaya Mencangkok Tanaman Di Desa Banyumulek, Kecamatan Kediri, Kabupaten Lombok Barat, Nusa Tenggara Barat - Muhamad Arju Gupron; Nasria Ningsih; Lalu Wahyu Nanda Farisky; Muktar; Andri Azmul Fauzi; Melinda Pahriana Sulastri (Aksi: Jurnal Pengabdian Masyarakat, 2024)
Grafting is a vegetative propagation technique that has long been used by people to maintain and develop superior quality plants. This technique has great benefits, especially in ensuring genetic uniformity and quality of the fruit produced. The method used in this research is a qualitative approach with participatory techniques. In community service activities in Banyumulek Village, we teach grafting techniques to local residents in the hope that they can practice them to reproduce fruit plants with high economic value. This activity is carried out through a participatory approach, where the community is invited directly to try grafting plants using simple but effective materials and tools. Some of the materials used in this process include a knife or cutter to peel the bark of the plant stem, planting medium in the form of fertile soil and compost, and plastic or coconut fiber which functions to wrap the planting medium and maintain moisture.